2019
DOI: 10.1016/j.resuscitation.2019.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between socioeconomic factors, distribution of public access defibrillators and incidence of out-of-hospital cardiac arrest

Abstract: Background: Survival from out-of-hospital cardiac arrest (OHCA) is improved when public access defibrillators are used. Areas of socioeconomic deprivation may have higher rates of OHCA and thus a greater demand for public access defibrillators. We aimed to determine if there was a relationship between socioeconomic factors, the geographic distribution of public access defibrillators (PADs) and incidence of OHCA. . Relationships between these variables were analysed using a Poisson regression analysis.Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…19 Health inequities are well documented for Maori; rurality is one contributing dimension of this. 20 For both age and ethnicity, it is likely that the geographic location of the OHCA directly impacts on transport to a PCI-capable hospital. However, this study did not specifically investigate whether there was any bias on the part of attending ambulance crews or whether features of the cardiac arrest (shockable vs non-shockable rhythm, bystander CPR) could have influenced transport destination decisions.…”
Section: Discussionmentioning
confidence: 99%
“…19 Health inequities are well documented for Maori; rurality is one contributing dimension of this. 20 For both age and ethnicity, it is likely that the geographic location of the OHCA directly impacts on transport to a PCI-capable hospital. However, this study did not specifically investigate whether there was any bias on the part of attending ambulance crews or whether features of the cardiac arrest (shockable vs non-shockable rhythm, bystander CPR) could have influenced transport destination decisions.…”
Section: Discussionmentioning
confidence: 99%
“…In New Zealand the most socioeconomically deprived communities had the highest incidence of OHCA and the least availability of AEDs. 37 In the USA Zip codes that had high-access to AEDs also tended to have a higher median household income with a slightly higher proportion of the population being high school graduates, 16 and also a lower median residential population and a higher proportion of unemployed residents. In Seoul, more affluent neighbourhoods exhibit higher per capita AEDs, even when accounting for OHCA risk, with 4.92 AEDs per 10,000 in the lowest socio-economic status quartile and 12.66 per 10,000 in highest.…”
Section: Discussionmentioning
confidence: 99%
“…Respondents also currently use risk assessment methods to estimate the need for PADs in a given location to facilitate the best use of limited resources and benefit to communities. Some report taking a targeted approach placing PADs in deprived areas, which generally also have the highest rates of OHCA, 28 , 29 , 30 have lower rates of PAD deployment, 29 , 31 and have poorer OHCA survival outcomes. 3 , 32 , 33 , 34 A recent study in Scotland found poor alignment between PAD and OHCA locations across levels of socioeconomic deprivation as measured by the Scottish Index of Multiple Deprivation (SIMD): in particular, OHCAs in SIMD quintile 1 (including the most deprived communities) were least likely to have PADs.…”
Section: Discussionmentioning
confidence: 99%